Freshwater as a global commons: International governance and the role of Germany - Elke Herrfahrdt-Pähle; Waltina Scheumann; Annabelle Houdret; Ines Dombrowsky (Deutsches Institut für Entwicklungspolitik (DIE), 2019)
Water is essential for all life on earth and is a key prerequisite for attaining many of the Sustainable Development Goals (SDGs). Many countries, however, suffer from physical water scarcity, a lack of access to a safe water supply and sanitation, water pollution or hydrological extremes (droughts and floods) due to climate change. The generality and severity of water problems lead many to speak of a global water crisis. While this crisis mostly manifests at the local or in some cases transboundary level, two global issues are often overlooked. First, global trends such as climate change and the spread of water-intensive consumption and trade patterns are key triggers that cannot be addressed at the local level alone. Second, the aggregation of local or regional water problems may add up to a universal threat to sustainable development. In the face of current challenges, (fresh) water should be conceptualised as a global common good, and global water governance should contribute to improving its protection. [...]
Keywords: 330